PENGARUH CADANGAN KERUGIAN PENURUNAN NILAI (CKPN), JUMLAH KREDIT YANG DIBERIKAN, DAN KONDISI PERMODALAN TERHADAP PROFITABILITAS - Rada Eramina; Ni Ketut Muliasari (Universitas Dian Nuswantoro, 2023)
This research aims it know allowance for impairment losses as measured by loan loss provisioning, credit which given as measured by credit propotion, condition of capital as measured by the capital adequacy ratio, eficiency aperational as measured by operating Expenses to Operating Revenue and Liquidity as measured by loan to deposit ratio to profibility as measured by return on assets incompanies banking listed on OJK the for years 2018-2022. The sampling technique used in this research in purposive sampling method and obtain 28 banks. Types of data used was secondary data obtained from www.ojk.go.id analyzing data used a statistical data processing sofware EVIEWS 12.00 for windows. Based on the result of mutiple regression analyzing with a aignifiance level of 5%, the result of the study conclude: (1). Allowance for impairment losses has no effect on profitability on companies of banking listed on OJK with the ? coefficient is negative amounted to -0.033 and significant value 0.127 > 0.05, (2). Credit which given has a significant on profitability on companies of banking listed on OJK with the ? coefficient positive is -0.113 and significance value 0.127 < 0.05. (3). Condition of capital has on effect on profitability on companies of banking listed on OJK with the ? coefficient -0.113 and significance value 0.033 > 0.05.